Replacement of floor structures in capital repair with the use of not extractable void formers - Afanasyev, Grigoriy (E3S web of conferences, 2019)
Urgency of the floor structures replacement is driven by the program of capital repair of the residential buildings adopted by the government and stipulates replacement of wood coverings by armored concrete floors that enable increase of stability, fire-resistance and cost effectiveness. Wood partitions and other elements of planning made of materials with low fire-resistance are also subject to replacement. It has been shown that the use of void formers allows reducing consumption of concrete, reinforcement, reduces duration of building and energy consumption. Thereby the stability and fire-resistance increase of the buildings under renovation is achieved. Solving these tasks is the objective of the represented work. It is worth noting that when renovating buildings the data about the use of not extractable void formers are absent. The technology development is an author’s initiative. The goal of the investigations consists in analyzing the works of the domestic and foreign scientists that make it possible to assess effectiveness of the technology when erecting buildings of cast in-situ reinforced concrete with the use of void formers. The submitted work has carried out the adaptation of the works performance technology in confined spaces of capital repair. Optimization of the void formers selection has been made, node points of the slabs’ resting on brick walls have been developed, the technology of dismantlement, form work, reinforcing, installation of void formers and concrete pouring has been developed. The complex of the works provides for obtainment of floor structures with the lesser consumption of concrete and reinforcement..